2001
DOI: 10.1074/jbc.m100272200
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Activity-induced Transcriptional Activation of Cytochrome c Involves Sp1 and Is Proportional to Mitochondrial ATP Synthesis in C2C12 Muscle Cells

Abstract: Contractile activity induces adaptations in the expression of genes encoding skeletal muscle mitochondrial proteins; however, the putative signals responsible for these adaptations remain unknown. We used electrical stimulation (5 Hz, 65 V) of C2C12 muscle cells in culture to define some of the mechanisms involved in contractile activity-induced changes in cytochrome c gene expression. Chronic contractile activity (4 days, 3 h/day) augmented cytochrome c mRNA by 1.6-fold above control cells. This was likely me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…Before the first bout of contractile activity, DMSO (Sigma) or 1 M rapamycin (BioShop, Toronto, ON, Canada) was added to the media. The protocol for CCA has been described previously in detail (8,42). Briefly, customized six-well plate lids were outfitted with two platinum wires per well and were submerged into the media of plates containing fully differentiated myotubes.…”
Section: Methodsmentioning
confidence: 99%
“…Before the first bout of contractile activity, DMSO (Sigma) or 1 M rapamycin (BioShop, Toronto, ON, Canada) was added to the media. The protocol for CCA has been described previously in detail (8,42). Briefly, customized six-well plate lids were outfitted with two platinum wires per well and were submerged into the media of plates containing fully differentiated myotubes.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to primary cultures, confluent myoblast cultures of both cell lines can be induced to form myotubes, but only C2C12 myotubes can be induced to contract by electrical stimulation. Methods have been developed to stimulate C2C12 myotubes chronically or intermittently for up to 4 days using stimulus electrodes integrated in standard culture dishes (718,723). This technique allows a more detailed analysis of the interaction between thyroid hormone and contractile activity on muscle gene expression (718).…”
Section: And Recommendation 65mentioning
confidence: 99%
“…Several studies have demonstrated that changes in the mRNA expression of transcription factors precede the contractile activity-induced regulation of mitochondrial and metabolic plasticity in skeletal muscle (Connor et al, 2001;Irrcher et al, 2003;Michel et al, 1994;Pilegaard et al, 2003;Xia et al, 1997). These include the induction of a family of immediate early genes (c-fos, c-jun), the early growth response gene-1 (Egr-1), specificity protein 1 (Sp1) and nuclear respiratory factor-1 (NRF-1), which respond to both acute and chronic contractile activity (Abu-Shakra et al, 1993;Connor et al, 2001;Irrcher and Hood, 2004;Michel et al, 1994;Murakami et al, 1998;Neufer et al, 1998;Puntschart et al, 1998;Takahashi et al, 1993).…”
Section: Gene Expression Response To Contractile Activity and Recoverymentioning
confidence: 99%
“…Several studies have demonstrated that changes in the mRNA expression of transcription factors precede the contractile activity-induced regulation of mitochondrial and metabolic plasticity in skeletal muscle (Connor et al, 2001;Irrcher et al, 2003;Michel et al, 1994;Pilegaard et al, 2003;Xia et al, 1997). These include the induction of a family of immediate early genes (c-fos, c-jun), the early growth response gene-1 (Egr-1), specificity protein 1 (Sp1) and nuclear respiratory factor-1 (NRF-1), which respond to both acute and chronic contractile activity (Abu-Shakra et al, 1993;Connor et al, 2001;Irrcher and Hood, 2004;Michel et al, 1994;Murakami et al, 1998;Neufer et al, 1998;Puntschart et al, 1998;Takahashi et al, 1993). Egr-1 and Sp1 are known to be involved in regulating the transcription of cytochrome c, a nuclear-encoded protein of the electron transport chain (Connor et al, 2001;Freyssenet et al, 2004), while NRF-1 is involved in the transcriptional activation of an even greater diversity of nuclear genes encoding mitochondrial proteins (Kelly and Scarpulla, 2004), including the newly discovered mtDNA transcription factors TFB1M and TFB2M (Gleyzer et al, 2005).…”
Section: Gene Expression Response To Contractile Activity and Recoverymentioning
confidence: 99%
See 1 more Smart Citation